Pengaruh Rasio Kecukupan Modal dan Margin Bunga Bersih Terhadap Tingkat Pengembalian Aset - Dini Fauziah; Nana Diana (Jurnal Dinamika Ekonomi & Bisnis, 2022)
This research aims to determine the effect of the capital adequacy ratio and net interest margin on the rate of return on assets at state-owned banks for the 2014-2021 period. In sampling using saturated samples. Sample data obtained from the bank's website. The technique used is multiple linear regression analysis. The result of the research is that partially, the capital adequacy ratio does not significantly affect the rate of return on assets, while the net interest margin significantly affects the rate of return on assets. Simultaneously, these two variables have an influence on the rate of return on assets.